Rare earth identification from electronic waste : solid phase separation (acid leaching) - Nur Ashikin, Jamin (2015)
Rare earth element (REE) commonly used as a significant component in electronic appliance such as Liquid-crystal display (LCD). Nowadays, rare earth element is being disposed rather than being recycled or reused. Due to the increased in demand, rare earth element become more economically profitable. Recycling or recovery of rare earth element from electronic waste will help to secure the effect on price, supply and quantity of the element. The aim of this research is to identify the rare earth element contain in the LCD. The separation process of solid phase extraction (SPE) or so called as leaching method were introduced to identify the rare earth in the LCD. The concentration of acid solution parameter was varied to examine the optimum condition for leaching process of LCD by chromatography analysis using X-ray Diffraction (XRD).